Morphology and properties of polybutylene succinic and cassava starch blend: Effect of esterification catalysts on graft copolymer formation. Issue 1 (29th March 2021) - Duc, Vu Minh; Giang, Nguyen Chau
Abstract: The purpose of this research is to produce of esterified thermoplastic starch (ETPS) for reactive extrusion melt‐blending with polybutylene succinate (PBS) in film blowing application. Esterification TPS named M‐TPS and T‐TPS were prepared from cassava starch, glycerol (plasticizer), and maleic anhydride (MA), tartaric acid (TA) as reactive compatibilizers in a twin extruder, respectively. FTIR results showed that esterification reactions were successfully formed between both MA and TA with cassava starch. The esterified TPSs was then melt blended with PBS in the presence of four kinds of esterification catalysts. The effect of compatibilizer contents on the blend properties was studied in terms of tensile properties, melt flow index (MFI), and electron scanning microscopy (SEM). The results show that TA induced better compatibilization effect than MA did, as evidenced by the PBS/T‐TPS blend possessing higher strength than these of PBS/M‐TPS, although SEM images showed structural morphology of both blends is similar. The effect of the esterification catalyst type and contents on properties of the PBS/T‐TPS blend was also studied. The results from the Molau test confirmed the formation of graft‐copolymer (PBSgT‐TPS) at the interface of two phases of the blend when compatibilizers were added in the presence of an organotin compound catalyst.